Analysis of seaports efficiency in supporting inter-island transportation - Adenanthera L Dewa; Nugroho SBM; Mudjahirin Thohir; Indah Susilowati (Economic Journal of Emerging Markets, 2018)
This study analyzes the efficiency of 15 ports in Indonesia that connect the islands;users' perceptions on the needs of sea transport facilities both in ships andterminals; and a network of passenger facility needs based on preference. Theresearch uses the sequential mixed method. The results show that 4 of the 15 portsamples have not yet reached efficiency. The main reasons why users choose shipsare because ships have complete facilities and are therefore more convenient,allow them to carry more goods, at affordable ticket prices, and users usuallytravel in groups. Users are most concerned with and want complete facilities,comfort, safety and order, viability and accessibility to reach the ports and boardthe ships.